Similarities and Differences in Maternal Responsiveness in Three Societies: Evidence From Fiji, Kenya, and the United States. Issue 3 (May 2016) - Broesch, Tanya; Rochat, Philippe; Olah, Kata; Broesch, James; Henrich, Joseph
Abstract : The first relationship between an infant and her caregiver, typically the mother, lays the foundation for cognitive, social, and emotional development. Maternal responsiveness and affect mirroring have been studied extensively in Western societies yet very few studies have systematically examined these caregiving features in non‐Western settings. Sixty‐six mother–infant dyads (7 months, SD = 3.1) were observed in a small‐scale, rural island society in Fiji, a village in Kenya, and an urban center in the United States. Mothers responded similarly to infant bids overall, but differences were found across societies in the ways mothers selectively respond to affective displays. This has implications for understanding early emotion socialization as well as understanding variation in infant social ecologies across the globe.